Correlation between pancreatic polypeptide response to secretin and ERCP findings in chronic pancreatitis. Issue 3 (March 1982) - Stern, I; Roberts-Thomson, I C; Hansky, J
Abstract : Previous studies have shown an impaired pancreatic polypeptide response to secretin in most patients with advanced chronic pancreatitis, but the sensitivity of the investigation in milder degrees of chronic pancreatitis remains unclear. In the present study the pancreatic polypeptide response to secretin was evaluated in 32 patients categorised as having advanced, moderate, or minimal chronic pancreatitis on the basis of the degree of abnormality of the retrograde pancreatogram. The pancreatic polypeptide response was abnormal (peak:basal pancreatic polypeptide ratio less than 5) in 17 of 19 patients (90%) with advanced or moderate chronic pancreatitis, but was normal in patients with minimal disease. The simple and non-invasive nature of this test makes it an attractive investigation for evaluation of the severity of pancreatic damage.